2013
DOI: 10.1111/dme.12060
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported outcomes of trans‐tibial amputations for non‐reconstructable Charcot neuroarthropathy in patients with diabetes: a preliminary report

Abstract: In a select group of Charcot neuroarthropathy patients with chronic osteomyelitis, trans-tibial amputation resulted in improvement in self-reported outcomes. Although major lower-extremity amputation is a devastating complication in patients with diabetes, the results of this study provides some evidence for optimism in these high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 16 publications
0
14
0
1
Order By: Relevance
“…The combination of the SF-36 and FAAM has been used in several studies of diabetic foot disease (2832). Our patients normally require approximately 15 minutes to complete the SF-36, and we expected that <5 minutes would be required to complete the SF-12.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of the SF-36 and FAAM has been used in several studies of diabetic foot disease (2832). Our patients normally require approximately 15 minutes to complete the SF-36, and we expected that <5 minutes would be required to complete the SF-12.…”
Section: Discussionmentioning
confidence: 99%
“…This osseous destructive process can result in foot deformity, ulceration, infection, hospitalization, and, in some cases, major amputation (4,5). Patients with DM are also at increased risk of developing peripheral arterial disease (PAD).…”
mentioning
confidence: 99%
“…We observed 5 patients (24%) with the need for amputation leading to an annual amputation rate of 6%. These high rates are relativized by the recent finding of Wukich and Pearson [ 37 ] who actually reported an improvement of neuropathic patients' self-reported quality of life following transtibial amputation. Our amputation rates are in line with Saltzman et al [ 23 ] who reported, for a cohort of 115 patients and a 3.8-year follow-up, an annual amputation risk of 3% without and an amputation risk of 28% with ulceration present initially, as well as a 23% risk of requiring more than 18 months casting and a high risk of about 49% for recurrent ulceration.…”
Section: Discussionmentioning
confidence: 99%